PENGARUH KUALITAS KEHIDUPAN KERJA DAN KOMITMEN ORGANISASI TERHADAP KINERJA PEGAWAI PADA PDAM TIRTANADI CABANG PADANG BULAN - MALUDIN PANJAITAN (Sekolah Tinggi Ilmu Ekonomi Dr Kh Ez Mutaqien, 2022)
Employee performance is the work achieved by a person or group of people in accordance with the authority or responsibility of each employee during a certain period. Many factors affect employee performance, including quality of work life and organizational commitment. This research is a quantitative study with a cross sectional approach which aims to analyze the effect of quality of work life and work commitment on the performance of PDAM Tirtanadi employees, Padang Bulan Branch, Medan. The population is all employees of PDAM Tirtanadi Padang Bulan Branch totaling 137 people. Determination of the sample using the Slovin formula so that there are 58 samples. Data analysis used multiple linear regression which included simultaneous F test, partial t test, R2 determination test and regression equation. The results showed that the quality of the work environment partially gave a significant influence on employee performance. Organizational commitment partially has a significant effect on employee performance. The qualities of work environment and organizational commitment have a positive and significant effect on employee performance. It is suggested to PDAM Tirtanadi Medan to pay more attention to aspects that affect employee performance such as the quality of the work environment and organizational commitment so that employee performance can be further improved.